Chandra and XMM‐Newton: Synergies now and in the future. Issue 2 (21st March 2017) - Wilkes, B. J.
Abstract : In 1999, two world‐class X‐ray observatories were successfully launched and began operation, ushering in the golden age of X‐ray astronomy: National Aeronautics and Space Administration's Chandra, and European Space Agency's XMM‐Newton. Over the past 17 years, both satellites have operated with remarkable reliability and have revolutionized X‐ray astronomy. Our knowledge of the X‐ray universe, a hot and often violent place, has snow‐balled, and with it our understanding of many celestial sources. The community has expanded to include a large fraction of astronomers worldwide, and discoveries cover almost every area of astronomical research. With no clear lifetime issues, at least a decade more of ground‐breaking observations is anticipated. Now is a good time to take stock of our progress and look to the future, to ensure XMM‐Newton's legacy, to focus on X‐ray science that has not yet been completed, and to prepare to take full advantage of the opportunities for new and expanded studies that are now or will soon become available as new observatories come on line.